Assessment of the anterior loop of mental nerve in an Iranian population using cone beam computed tomography scan - Mitra Karbasi Kheir; Mahnaz Sheikhi (Wolters Kluwer Medknow Publications, 2017)
Background: The anterior loop is an important structure in the interforaminal area of the mandible. The aim of the present study was to assess the prevalence and length of the anterior loop of mental nerve using cone beam computed tomography (CBCT) scan and to compare the differences between age, gender, and side. Materials and Methods: A total of 180 projections were analyzed in different sectional planes. The inferior alveolar nerve was determined. To measure the length of anterior loop in tangential plane, two parallel lines from the anterior point of mental foramen and anterior point of anterior loop were drawn. The distance between these two lines was measured by drawing a perpendicular line on them. The data were analyzed by SPSS (version 22). McNemar's test, Chi-square test, and t-test were performed to compare the significance of findings regarding side, age, and gender. P < 0.05 was considered statistically significant. Results: The results showed that 32.8% of images had anterior loop. The mean lengths of anterior loop in the right and left sides were 2.69 mm (standard deviation [SD] = 1.56) and 2.36 mm (SD = 1.16), respectively. There were no statistically significant differences between the mean lengths of the anterior loop in both sides (P = 0.18). Conclusion: Great care is required when placing implants in proximity to mental foramen to avoid anterior loop injury. Because of the variations of anterior loop length in each patient, a fixed distance anterior to the mental foramen is not safe, and the anterior loop length should be determined for each individual. The use of CBCT provides accurate measurements of the length of anterior loop.